Exploring the possibilities of two-dimensional transition metal carbides as anode materials for sodium batteries1. Issue 7 (21st February 2015) - Yang, Eunjeong; Ji, Hyunjun; Kim, Jaehoon; Kim, Heejin; Jung, Yousung
<x xml:space="preserve">Abstract</x> MXenes are predicted to be a family of promising Na anode materials with desirable electrochemical properties using density functional theory.